Mood-induction research--its implications for clinical depression. - Goodwin, A; Williams, J (1982)
Mood-induction procedures (MIPs) are increasingly being used as laboratory analogues of clinical depression. Four methods of mood induction are described: reading depressing self-referent statements: remembering past unpleasant events; listening to a taped depressing story: and failure on a task. The effects of these MIPs on affect, behaviour and related variables and parallels between these effects and clinical deficits are reviewed. The implications of MIP research for clinical depression are discussed in the light of self-awareness theory, mood effects on memory, and the inter-relationship between cognitive and somatic variables in depression. © 1982.